2014
DOI: 10.1128/jcm.02860-13
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Dried Blood Spots for Routine HIV-1 Viral Load and Drug Resistance Monitoring in Patients Receiving Antiretroviral Therapy in Africa and Asia

Abstract: h Dried blood spots (DBS) can be used in developing countries to alleviate the logistic constraints of using blood plasma specimens for viral load (VL) and HIV drug resistance (HIVDR) testing, but they should be assessed under field conditions. Between 2009 and 2011, we collected paired plasma-DBS samples from treatment-experienced HIV-1-infected adults in Burkina Faso, Cameroon, Senegal, Togo, Thailand, and Vietnam. The DBS were stored at an ambient temperature for 2 to 4 weeks and subsequently at ؊20°C befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 25 publications
3
49
1
2
Order By: Relevance
“…In previous studies performed with the Abbott system, sensitivity for the detection of virological failure at 1 000 copies/mL was between 75% and 100% and specificity was between 82% and 97%. [10,11] In our study, very high positive and negative predictive values were observed when using a threshold of 1 000 copies/mL, suggesting that even with the use of DBS the threshold of 1 000 copies/mL can provide reliable results, given the specificity of 98.6% at this threshold.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In previous studies performed with the Abbott system, sensitivity for the detection of virological failure at 1 000 copies/mL was between 75% and 100% and specificity was between 82% and 97%. [10,11] In our study, very high positive and negative predictive values were observed when using a threshold of 1 000 copies/mL, suggesting that even with the use of DBS the threshold of 1 000 copies/mL can provide reliable results, given the specificity of 98.6% at this threshold.…”
Section: Discussionmentioning
confidence: 55%
“…[5] The modest overquantification that we observed with DBS can be ascribed to the presence of HIVDNA and intracellular RNA and seems to have a greater impact on samples with a low viral load (in our study <3 000 copies/mL), as previously reported. [4,11,14] The 2013 HIV treatment guidelines of the World Health Organi zation [15] indicate a threshold of 1 000 copies/mL of HIVRNA to define virological failure using plasma, and suggest use of a higher, although undefined, threshold when using DBS. In previous studies performed with the Abbott system, sensitivity for the detection of virological failure at 1 000 copies/mL was between 75% and 100% and specificity was between 82% and 97%.…”
Section: Discussionmentioning
confidence: 99%
“…For 92 of them, the date between symptom onset and blood sampling was known and the median interval between these two dates was 350 days (interquartile range [IQR]: 293 to 421 days). For each patient, five spots of 50 l of whole blood were prepared as described previously (31). Plasma was reconstituted from one DBS spot in 1 ml of incubation buffer, consisting of phosphate-buffered saline (PBS) containing 0.75 mol/liter of NaCl, 1% (wt/vol) bovine serum albumin (Sigma-Aldrich, St. Quentin Fallavier, France), 5% (vol/vol) fetal bovine serum (Gibco-Invitrogen, Cergy Pontoise, France), and 0.2% (vol/vol) Tween 20 (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that DBS specimens may be useful for early diagnosis of pediatric HIV-1 infection, treatment monitoring, external quality assessment programs, and resistance testing (2)(3)(4). HIV-1 RNA testing on whole blood collected on DBS is highly effective in determining viral failure at the clinical threshold of 5,000 copies/ml and may be used effectively at a threshold of 1,000 copies/ml, although a suboptimal sensitivity was reported for this level (5).…”
mentioning
confidence: 99%
“…Fifty microliters of blood collected on EDTA tubes was spotted onto five 12-mm circles on a Whatman 903 filter paper card (Whatman GmbH, Dassel, Germany) and air dried for 1 day prior to storage at Ϫ20°C. For elution, two entire 12-mm spots were placed in 2.0 ml of lysis buffer under constant shaking for 1 h as previously described (2). DBS HIV-1 RNA was then extracted by the NucliSENS miniMag extraction system (bioMérieux, Marcy l'Etoile, France) or by the large-volume nucleic acid extraction kit using the Arrow extraction system (Biocentric, Bandol, France).…”
mentioning
confidence: 99%